The Effect Of Transparency And Accountability On The Performance Of Employees Of PT Bank Sumut KC Syariah Tebing Tinggi - Indri Lestari; Maya Sari (Al-Sharf: Jurnal Ekonomi Islam, 2021)
Performance in daily life can be interpreted as an ability that exists in each individual to complete work according to their responsibilities to get good work results. Employee performance is very important for the survival of a company to achieve prosperity for every employee or stakeholder in the company. To find out how the simultaneous influence of transparency and accountability on the performance of employees of PT. Bank SUMUT KC. Syariah Tebing Tinggi. The type of research used in this research is quantitative research. The location of this research is PT. Bank SUMUT Sharia Branch Office Tebing Tinggi, Jln.Dr. Sutomo No. 21 Kota Tebing Tinggi, the sample to be taken from employees at PT. Bank SUMUT KC Syariah Tebing Tinggi is a total of 30 people, the data analysis technique used in this study is the linear regression method (multiple regression analysis), while the result of this research is that transparency has an influence on employee performance. Accountability has a significant and significant effect on performance. In this study together, Transparency and Accountability have an effect and are significant on employee performance.